Implementation of Mentoring System through Digital Application to Improve Nurse Quality in Hospital - Yureya Nita, Yeni Devita, Martina Sinta Kristanti (South Eastern European Journal of Public Health, 2025)
The process of enhancing one's own quality of life through education and an emotional bond between mentors and mentees is known as mentoring. Mentoring activities in nursing positively affect nurses' motivation at work, namely as a support to increase nurses' job satisfaction.The purpose of this study was to analyse how the implementation of mentoring of mentor nurses to mentee nurses in hospitals using the ‘Si-Mantap’ system. PenelitianThis study was conducted at ArifinAchmad Hospital, Riau Province, from May to October 2024. The sample in this study was 162 mentee nurses. The research method useda descriptive-analytic design to see the variables of age, length of service, education, and nurse mentoring evaluation categories: career support, psychosocial support, and role models. The research results on the characteristics of nurses from 162 nurses found more nurses of Young Adult age (18-44 years), 91%, more nurses of 0 - 10 years of work, 72%, and more nurses with Ners education, 62%. The evaluation of the nurse mentoring system showed that there were more nurses in the Exemplary category, 85.2%. This shows that nurse mentors as role models for mentees are very influential in nursing care in hospitals. This study concludes that the ‘Si Mantap’ application mentoring system carried out by mentors greatly influences the improvement of the quality of nurses in hospitals.